(untitled) (Engineering Review, 2024)
The conventional quasi-z-source inverter (QZSI) is not capable of producing DC-side voltage gain without shoot-through operation. This restricts freedom of control and performance. The decoupled control between modulation index (MI) and duty ratio for producing DC-side voltage gain at MI = 1 is not permitted. In this context, this paper proposes a novel active-switched impedance network. This is capable of producing DC-side voltage gain either in shoot-through mode or in the absence of shoot-through state. In effect, variable DC-side voltage gains are achieved at a fixed value of MI, even at MI = 1 (without the dead-time requirement of the inverter bridge). For low-gain operations (up to 2.5), the DC-side voltage gain is achieved by the proposed active-switched QZSI by restricting the shoot-through duty ratio to a low value (0-0.1). In high-gain (>2.5) operations, the variable-boosting operations of the proposed QZSI are achieved without shoot-through operation (MI = 1) by controlling its active switch. This increases efficiency by discarding the shoot-through state at high gain. The suggested closed-loop control logic of the proposed QZSI is also provided to meet the load voltage. The simulation work is conducted in versatile operating conditions to highlight its diversified performances. The experiments also verify its operations under different conditions.